Genotype and Phenotype Detection of E. coli Isolated from Children Suffering from Urinary Tract Infection - Zahraa Hameed Oda Alquraishi (Journal of Global Pharma Technology, 2018)
One hundred clinical urine samples were obtained from patients suffering from UTI during the period from 1, August, 2017 to 9, October, 2017. Methodology: The identification of the E. coli isolates was depended on colonial morphology, microscopic examination and biochemical tests as a primary identification. The final identification was performed by PCR technique with Mdh. In addition antibiotic genes were used such as (bla-CTM, blatem-1, aac (6) - Ib-crandsul-1). Result: Rendering to the results obtained according to the morphological ,cultural and biochemical characters from 100 sample only 80 (80%) isolate was identify as E. coli. According to the results obtained by PCR, Mdh gene that encode was found in 56 (70%) isolates in E. coli. The results of PCR revealed that the percentage of bla-CTX-M gene among tested isolates reached to 30/56(53.57%), 10/56(17.85%) for blaTEM-1, 13/56(23.2%) for aac (6’)-Ib –cr and 33/42 (78.57%) for Sul-1gene. Conclusion: The study investigated the antibiotic resistance genes of E. coli which play a major role in pathogen city .Keywords: E. coli, Urinary tract infection and antibiotic resistance genes.